Revealing the complete mitochondrial genome of Thermophis baileyi Wall, 1907 (Reptilia: Colubridae) through the next-generation sequencing. Issue 2 (12th December 2017) - Sun, Feng-Hui
Abstract: The complete mitochondrial genome of Thermophis baileyi was sequenced using the next-generation sequencing (NGS) in the present study. The total length of the mitogenome was 17, 355 bp, which was composed of 13 protein-coding genes, 22 transfer RNA (tRNA) genes, 2 ribosomal RNA (rRNA) genes (12s and 16s rRNA), and 2 control regions (CR I and CR II). The base composition was 32.4% for A, 23.8% for T, 30.2% for C, and 13.6% for G. Coding genes of each protein in the mtDNA had the same start and stop codons among three Thermophis species.